A Diagnostic Challenge in The Emergency Department: Dysarthria-Clunky Hand Syndrome. - Pozos Gutiérrez, Dr. Eric Miguel; Mendez de Jesus, Dr. Ignacio Alberto; Orejel Feria , Dr. Tabatta Gabriela; Dawn Martínez, Dr. Iliana Patricia; Fajardo Cervantes , Dr. Jackeline; Hernández Sánchez, Dr. Diana (Clinical Medicine And Health Research Journal, 2023)
Background: Small vessel vascular disease can present as different entities including lacunar infarctions. Dysarthria-clumsy hand syndrome is the rarest classic lacunar syndrome, this syndrome is described as the combination of dysarthria with clumsiness of the hand, manifested as slowing in fine manipulation, difficulty in writing, along with hesitant ataxia in the finger-nose test that differed from the cerebellar type. Clinical case: A 59-year-old female attended the continuous admission service due to acute neurological deterioration characterized by dysarthria and right hemiparesis, performing a neurological physical examination where moderate dysarthria was evident, slight deviation of the left labial commissure, decreased strength in the right upper extremity, latero drive of the march to the right, in angiotomographic study it was reported absence of flow in left perforating artery, Diagnosis of lacunar ischemic vascular event, dysarthria-clumsy hand syndrome. Conclusions: Dysarthria-clumsy hand syndrome is a rare syndrome with a good prognosis, however, as first contact physicians we must be prepared for the different variants of cerebrovascular disease that may present to the emergency area, never delaying the diagnosis with a view to early treatment to limit the damage.